Lung epithelial cells are essential effectors of inducible resistance to pneumonia - Cleaver, J O; You, D; Michaud, D R; Guzmán Pruneda, F A; Leiva Juarez, M M; Zhang, J; Weill, P M; Adachi, R; Gong, L; Moghaddam, S J; Poynter, M E; Tuvim, M J; et al. (Mucosal immunology, 2014)
Infectious pneumonias are the leading cause of death worldwide, particularly among immunocompromised patients. Therapeutic stimulation of the lungs' intrinsic defenses with a unique combination of inhaled Toll-like receptor (TLR) agonists broadly protects mice against otherwise lethal pneumonias. As the survival benefit persists despite cytotoxic chemotherapy-related neutropenia, the cells required for protection were investigated. The inducibility of resistance was tested in mice with deficiencies of leukocyte lineages due to genetic deletions and in wild-type mice with leukocyte populations significantly reduced by antibodies or toxins. Surprisingly, these serial reductions in leukocyte lineages did not appreciably impair inducible resistance, but targeted disruption of TLR signaling in the lung epithelium resulted in complete abrogation of the protective effect. Isolated lung epithelial cells were also induced to kill pathogens in the absence of leukocytes. Proteomic and gene expression analyses of isolated epithelial cells and whole lungs revealed highly congruent antimicrobial responses. Taken together, these data indicate that lung epithelial cells are necessary and sufficient effectors of inducible resistance. These findings challenge conventional paradigms about the role of epithelia in antimicrobial defense and offer a novel potential intervention to protect patients with impaired leukocyte-mediated immunity from fatal pneumonias.